The Effect of Splitting on Reducing Pain Scale in Closed Fracture Patients at Grandmed Hospital Lubuk Pakam - Sitepu, Abdi Lestari (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
A splint is one of the nursing interventions used to fixate or immobilize injured body parts, particularly in cases of fractures. The primary function of a splint is to stabilize bone fragments and prevent displacement that may worsen the patient’s condition. In fractures, pain arises not only from tissue, nerve, and vascular damage but also from the uncontrolled movement of bone fragments. This pain can affect the cardiovascular, endocrine, respiratory, and immune systems, and may trigger both physiological and psychological stress. Therefore, pain management is a crucial component of fracture care and can be addressed through pharmacological interventions such as analgesics, as well as non-pharmacological methods, including splinting. This study aimed to examine differences in pain scores among fracture patients before and after splint application. A quantitative design with a one-group pretest-posttest approach was employed. The sample consisted of 25 respondents selected using purposive sampling. Pain scale observations were conducted before and after the intervention, and data were analyzed using the Paired Sample T-Test with a significance level of 0.05. The results showed a probability value of p = 0.000 (p < 0.05), indicating a significant difference between pretest and posttest pain scores. It can be concluded that splint application has a significant effect in reducing pain levels among patients with closed fractures at Grandmed Hospital, Lubuk Pakam.